1999
DOI: 10.1016/s0014-5793(99)01183-7
|View full text |Cite
|
Sign up to set email alerts
|

NMR structure of the mature dimer initiation complex of HIV‐1 genomic RNA

Abstract: The two identical genomic RNA strands inside each HIV-1 viral particle are linked through homodimerization of an RNA stem-loop, termed SL1, near their 5P P ends. SL1 first dimerizes through a palindromic sequence in its loop, forming a transient kissing-loop complex which then refolds to a mature, linear duplex. We previously reported the NMR structure of a 23-base truncate of SL1 in kissing-dimer form, and here report the high-resolution structure of its linear isoform. This structure comprises three short du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
32
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 20 publications
4
32
0
Order By: Relevance
“…As an application of the model, we will study the energy landscape of the HIV-1 dimerization initiation signal (DIS), which shows the kissing-loop dimer and the extended-duplex dimer coexisting in thermal equilibrium. The theoretical predictions are consistent with the two forms of RNA-RNA complexes observed in crystal and NMR structural measurements (Mujeeb et al 1998(Mujeeb et al , 1999Ennifar et al 1999Ennifar et al , 2001Takahashi et al 2005;Ulyanov et al 2006).…”
Section: Introductionsupporting
confidence: 82%
“…As an application of the model, we will study the energy landscape of the HIV-1 dimerization initiation signal (DIS), which shows the kissing-loop dimer and the extended-duplex dimer coexisting in thermal equilibrium. The theoretical predictions are consistent with the two forms of RNA-RNA complexes observed in crystal and NMR structural measurements (Mujeeb et al 1998(Mujeeb et al , 1999Ennifar et al 1999Ennifar et al , 2001Takahashi et al 2005;Ulyanov et al 2006).…”
Section: Introductionsupporting
confidence: 82%
“…In these complexes, base complementarity exists not only between the intermolecular hairpin loops, but also between the stem regions. In the case of the dimer initiation complex of the HIV-genomic RNA, a metastable intermolecular kissing interaction culminates in a linear duplex isoform stabilized by intermolecular base pairing (20,44). A kissing interaction also initiates the binding of the antisense RNA CopA to its target, CopT, but the outcome of this interaction is an unusual four-way junction defined by the predicted base stacking arrangements of intramolecular helices and newly formed intermolecular helices (19,45).…”
Section: Discussionmentioning
confidence: 99%
“…Kissing complexes in which the loop nucleotides are complementary can form stable dimers that contain intermolecular base pairs between the loop nucleotides only. Other stem-loops with more extensive complementarity sometimes form unstable kissing complexes, which are quickly remodeled into stable duplex or cruciform isoforms (18)(19)(20). Secondary structure remodeling involves breaking intramolecular base pairs in each hairpin and using the bases to form intermolecular helices.…”
mentioning
confidence: 99%
“…These latter changes may either affect the appropriate presentation of the palindrome within the loop, which is needed to initiate RNA dimerization, or prevent the transition of RNA dimers from the loose to the stable form. Detailed structures of the RNA dimer formed by SL1 have shown that both loop and stem sequences contribute to stabilization of the RNA duplex (11,12,14,35,36,49). As an example, the loop region contains three adenine residues that cannot form base pairs within the dimer and, as a consequence, might be expected to distort the RNA duplex.…”
mentioning
confidence: 99%